Application of Invisible Image Watermarking - Supiyandi, S; Lamudur Arta Sihombing, Grace; Kristian Siburian, Henry; Purnomo, Agung; Anam, Fatkul; Putut Laksminto Emanuel, Endrayana; Siregar, Dodi; Halim Putra, Aditya; E. Laumal, Folkes; Brillian Kharis, Oktaf; Akhiruddin, A; Rosnatang, R; et al. (International Journal of Engineering and Technology, 2018)
Copyright to an image is very important so that it is not misused by irresponsible parties, many ways can be done to provide copyright information in an image. Watermarking is a technique commonly used to mark a picture that the image already has copyright and whose owner is known, but in addition to visible watermarking there is also an invisible watermarking to indicate an image on a pixel or also in byte code and this is invisible. The Patchwork Algorithm is an algorithm that can be used to give an image to the image as an authenticity image so that many parties cannot claim it and are quite good from various modifications of image, application that has been created are purpose to embedded information as invisible watermarking in the image.Â